Hemato-biochemical, endocrine and in vitro immune competence of lactating Ghungroo sows during different days of lactation cycle - KALITA, BIDISHA; DAS, PRADIP KUMAR; GHOSH, PRABAL RANJAN; DAS, KINSUK; BANERJEE, DIPAK; NASKAR, SHYMAL; MUKHERJEE, JOYDIP (The Indian Journal of Animal Sciences, 2022)
Blood samples were collected from six Ghungroo sows on the day of farrowing, day 7, day 15, day 30, day 45 and day 60 post farrowing to investigate the alterations in the physio-biochemical, endocrine and in vitro activity of immune effector cells in Ghungroo sow during different days of lactation cycle. The hematological parameters were evaluated by standard hematological procedure. Blood biochemical and endocrine profiles were evaluated by commercially available kits. In vitro phagocytic activity and lymphocyte proliferation response were evaluated by colorimetric NBT and MTT assay respectively. Haemoglobin, packed cell volume (PCV) and total erythrocyte counts (TEC) increased significantly during the early lactation periods from the day of farrowing. The lymphocyte numbers decreased significantly from the day of farrowing to the 1st week of lactation cycle. Blood glucose and cholesterol level decreased significantly from the day of farrowing till first week of lactation cycle. The phagocytic activity of neutrophils was significantly higher on the day of farrowing and decreased till 30th day of lactation. The T4 level was higher on the day of farrowing and decreased significantly till 15th day of lactation. The data obtained in our investigation will help to formulate the managemental and therapeutic interventions during the period of transition from gestation to lactation in sows.